Analytical models for channel potential, threshold voltage, and subthreshold swing of junctionless triple-gate FinFETs. (April 2016) - Hu, Guangxi; Hu, Shuyan; Feng, Jianhua; Liu, Ran; Wang, Lingli; Zheng, Lirong
Abstract: Analytical models for channel potential, threshold voltage, and subthreshold swing of the short-channel fin-shaped field-effect transistor (FinFET) are obtained. The analytical model results are verified against simulations and good agreements are observed. Analytical expressions for subthreshold swing, drain induced barrier lowering effect, and threshold voltage roll-off characteristics are presented. The explicit expressions for threshold voltage and subthreshold swing make the model useful in the practical applications of the device.